Critical reflections on "humane" meat and plant-based meat "alternatives" - Wesley Tourangeau; Caitlin Michelle Scott (Canadian Food Studies, 2022)
Canadians are among the top meat consumers in the world. Greenhouse gas emissions, biodiversity loss, animal stress and suffering, worker health and safety, and cardiovascular disease are among the multitude of issues tied to high rates of meat consumption. In response to rising concern and debate over the impacts of meat consumption, two sectors of the food industry have grown considerably in recent years: "humane" meat and plant-based meat "alternatives." The former attempts to ameliorate harms via more ethical farming practices, and the latter utilizes technological innovations to replace animal-based meat. In this article, we outline a dilemma wherein pathways to more sustainable and ethical food systems may require both an acceptance of these solutions and a push beyond them towards more complex, systemic changes. We conclude with a brief discussion of critical food guidance, and the potential roles of law, regulation, and policy in driving incremental but important changes.